2019
DOI: 10.3389/fmicb.2019.02016
|View full text |Cite
|
Sign up to set email alerts
|

The Community Structure of Picophytoplankton in Lake Fuxian, a Deep and Oligotrophic Mountain Lake

Abstract: Spatial and seasonal dynamics of picophytoplankton were investigated by flow cytometry over a year in Lake Fuxian, a deep and oligotrophic mountain lake in southwest China. The contribution of picophytoplankton to the total Chl-a biomass and primary production were 50.1 and 66.1%, respectively. Picophytoplankton were mainly composed of phycoerythrin-rich picocyanobacteria (PE-cells) and photosynthetic picoeukaryotes (PPEs). PPEs were dominant in spring, reaching a maximum cell density of 3.0 × 104 cell mL–1, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
4
3
0
Order By: Relevance
“…Agriculture is one of the main activities in Lake Cajititlán, so it is possible that the abundance of this bacterium is associated with the increase in the concentration of nutrients from fertilizers, mainly during the rainy season, which enhances the runoff of nutrients to the lake. This effect has been observed in several subtropical studies (Munch, 1980;Li et al, 2010;Shi et al, 2019).…”
Section: Dynamics and Abundance Of The Dominant Taxa Of Lake Cajititlánsupporting
confidence: 68%
See 1 more Smart Citation
“…Agriculture is one of the main activities in Lake Cajititlán, so it is possible that the abundance of this bacterium is associated with the increase in the concentration of nutrients from fertilizers, mainly during the rainy season, which enhances the runoff of nutrients to the lake. This effect has been observed in several subtropical studies (Munch, 1980;Li et al, 2010;Shi et al, 2019).…”
Section: Dynamics and Abundance Of The Dominant Taxa Of Lake Cajititlánsupporting
confidence: 68%
“…Chlorophyceae is a dominant class in tropical eutrophic shallow lakes, whereas Chrysophyceae is considered characteristic of oligotrophic and mesotrophic waters ( Kristiansen, 1985 ; Chellappa et al, 2008 ; Silva et al, 2014 ). However, its dominance in subtropical and eutrophic water bodies has been detected during the summer season, with its presence being associated with the addition of allochthonous nutrients ( Munch, 1980 ; Shi et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, previous studies conducted in Ireland Estuary and Bengal Bay noticed a positive tight coupling between pH and DO (O'Boyle et al, 2013;Shaik et al, 2017). The significant correlation between pH and phytoplankton (both TChla concentrations and picophytoplankton density) indicated that biological activities had a substantial effect on pH (Shi et al, 2019). In general, when any aquatic environment is governed by autotrophy, CO 2 is eliminated by photosynthesis, resulting in a rise in pH values.…”
Section: Discussionsupporting
confidence: 63%
“…Regrettably, understanding about the taxonomic composition of picoeukaryotic algae in freshwater systems is still largely lacking although there have been some very good recent inputs about the community composition and diversity of Peuk [ 4 , 24 , 55 , 59 ]. Diatoms are usually considered as a common part of microplankton (20–200 μm) but nearly 20 species of diatoms in marine systems have one of their cell dimensions below 3 μm [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peuk have been treated as a bulk assemblage for decades since most of the traditional approaches to PPP quantification (epifluorescence microscopy, flow cytometry) are deficient in taxonomic resolution [ 23 ]. More recently, molecular methods have exposed a wide diversity of Peuk and have started to fill knowledge gaps in their taxonomic diversity [ 24 26 ]. However, metabarcoding as a qualitative analysis does not provide data for the comparisons of the relative abundances among different taxonomic groups [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%